Implication Of Relationship Marketing On Loyalty With Brand Image As A Moderation Variable - Hani Budi Lestari; Defi Insani Saibil (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
Abstract To create customer loyalty, banks need to implement a relational marketing strategy. In addition to relationship marketing, the bank also needs to pay attention to the brand image that is considered, because the brand image is also the key to maintaining and increasing customer loyalty. This study aims to examine the effect of the variables of trust, commitment, and empathy which are dimensions of relationship marketing on customer loyalty with the brand image as a moderating variable. The research subjects used in this study were Generation Z customers of Bank Syariah Indonesia (BSI) which opened 105 respondents. This research uses a quantitative analysis method with the moderator regression analysis (MRA) method. The partial test results show that the trust and commitment variables significantly affect customer loyalty, while the empathy variable has no significant effect on customer loyalty. Furthermore, the test results also show that brand image is not able to moderate the effect of trust, commitment, and empathy variables on customer loyalty.Keywords: Relationship Marketing, Customer Loyalty, Brand Image.